Bacterial toxicity assessment of drinking water treatment residue (DWTR) and lake sediment amended with DWTR. (1st November 2016) - Yuan, Nannan; Wang, Changhui; Pei, Yuansheng
Abstract: Drinking water treatment residue (DWTR) seems to be very promising for controlling lake sediment pollution. Logically, acquisition of the potential toxicity of DWTR will be beneficial for its applications. In this study, the toxicity of DWTR and sediments amended with DWTR to Aliivibrio fischeri was evaluated based on the Microtox ® solid and leachate phase assays, in combination with flow cytometry analyses and the kinetic luminescent bacteria test. The results showed that both solid particles and aqueous/organic extracts of DWTR exhibited no toxicity to the bacterial luminescence and growth. The solid particles of DWTR even promoted bacterial luminescence, possibly because DWTR particles could act as a microbial carrier and provide nutrients for bacteria growth. Bacterial toxicity (either luminescence or growth) was observed from the solid phase and aqueous/organic extracts of sediments with or without DWTR addition. Further analysis showed that the solid phase toxicity was determined to be related mainly to the fixation of bacteria to fine particles and/or organic matter, and all of the observed inhibition resulting from aqueous/organic extracts was identified as non-significant. Moreover, DWTR addition not only had no adverse effect on the aqueous/organic extract toxicity of the sediment but also reduced the solid phase toxicity of the sediment. Overall, in practical application, the solid particles, the water-soluble substances transferred to surface water or the organic substances in DWTR had no toxicity or any delayed effect on bacteria in lakes, and DWTR can therefore be considered as a non-hazardous material. Graphical abstract: Highlights: DWTR's solid particles promoted bacteria luminescence. DWTR's aqueous/organic extracts had no toxic effect on bacteria. DWTR reduced sediments' solid phase toxicity to bacteria luminescence. DWTR addition had no effect on sediment's aqueous/organic extracts toxicity.